2021
DOI: 10.1186/s13321-021-00522-2
|View full text |Cite
|
Sign up to set email alerts
|

GNINA 1.0: molecular docking with deep learning

Abstract: Molecular docking computationally predicts the conformation of a small molecule when binding to a receptor. Scoring functions are a vital piece of any molecular docking pipeline as they determine the fitness of sampled poses. Here we describe and evaluate the 1.0 release of the Gnina docking software, which utilizes an ensemble of convolutional neural networks (CNNs) as a scoring function. We also explore an array of parameter values for Gnina 1.0 to optimize docking performance and computational cost. Docking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
397
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 359 publications
(406 citation statements)
references
References 52 publications
9
397
0
Order By: Relevance
“…Additional file 1 : Figure S5 compares per-class Pearson’s correlation coefficient obtained with AEScore (and reported in Fig. 4 ) using results obtained with GNINA [ 20 , 21 ], a CNN-based scoring function. We see that for most classes the Pearson’s correlation coefficient obtained with both methods is similar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional file 1 : Figure S5 compares per-class Pearson’s correlation coefficient obtained with AEScore (and reported in Fig. 4 ) using results obtained with GNINA [ 20 , 21 ], a CNN-based scoring function. We see that for most classes the Pearson’s correlation coefficient obtained with both methods is similar.…”
Section: Resultsmentioning
confidence: 99%
“…Additional file 1 : Figure S11 shows the variation in CNN-based predictions as a function of the angle of rotation for a particular complex. Data augmentation with random translations and rotations has proved to be essential to prevent overfitting and significantly improve training in CNN-based scoring functions [ 20 , 21 ], but this is computationally expensive—another advantage of our approach.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate identification of near-native binding poses from decoy poses is a prerequisite for many downstream simulation tasks, such as binding affinity prediction and SBVS. Over the last few years, a number of MLSFs for binding pose prediction have been reported [ 26 , 36 46 ]. Some of them were trained to explicitly predict the root-mean-square-deviation (RMSD) values of binding poses, while the others were trained to directly distinguish near-native poses from high-RMSD ones.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Francoeur et al reported a standardized dataset named CrossDocked2020 set with 22.5 million poses generated by docking ligands into multiple similar binding pockets to better mimic the real-world scenarios, and they comprehensively estimated the scoring and docking powers of their grid-based CNN models [ 42 ]. Based on the dataset and assessment results, they further released the 1.0 version of GNINA, which could be considered as the first publicly available docking software that integrated an ensemble of CNNs as a SF [ 46 ]. However, it seems that the dataset may be not so suitable for the large-scale assessment of SFs due to its complexity and randomness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to virtual screening, attempts have been made to generate molecules by directly optimizing a docking score [ 19 , 20 , 21 , 22 ]. Recently, Boitreaud et al [ 23 ] suggested the OptiMol approach based on binding energy optimization for drug design using a generative model and docking using adaptive sampling (CbAS) [ 24 ] to maximize the objective function.…”
Section: Introductionmentioning
confidence: 99%